2009
DOI: 10.1103/physrevlett.102.058101
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelasticity in Homogeneous Protein Solutions

Abstract: We probe the transport properties in protein solutions stable with respect to any, solid or liquid, phase separation as a step in the understanding of transport in the cytosol of live cells. We determine the mean-squared displacement of probe particles in the time range 10;{-3}-10 s in solutions of a model protein. The tested solutions exhibit significant elasticity at high frequencies, while at low frequencies, they are purely viscous. We attribute this viscoelasticity to a dense network of weakly-bound chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
128
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(132 citation statements)
references
References 38 publications
4
128
0
Order By: Relevance
“…Other studies in similar systems have also suggested that protein diffusion in crowded marginally entangled polymer solutions deviates from simple Fickian diffusion 15,24,[50][51][52][53] . This, however, remains somewhat controversial, as mobile obstacles are not expected to produce anomalous diffusion 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies in similar systems have also suggested that protein diffusion in crowded marginally entangled polymer solutions deviates from simple Fickian diffusion 15,24,[50][51][52][53] . This, however, remains somewhat controversial, as mobile obstacles are not expected to produce anomalous diffusion 23 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, they include blinking quantum dots (20)(21)(22)(23), or biologically relevant systems. The latter include subdiffusion of tracer particles in living biological cells (24)(25)(26)(27)(28)(29) or reconstituted crowding systems (30)(31)(32)(33), protein conformational dynamics (34), or the motion of bacteria in a biofilm (35). Here we show how the knowledge of the aging correlation function allows us to quantify the nonergodic behavior of the underlying process.…”
mentioning
confidence: 99%
“…It is seen from (2) that the damping force at time t is only relative with the damping coefficient and instantaneous velocity at time t. But in some viscoelastic mediums [29][30][31][32][33][34], the damping force shows the property of ''fading memory'' [27], that is, the nearest velocity gives the highest impact on damping force, and the farthest is nearly close to zero. Here, the memory kernel of viscoelasticity [29,53] is given by…”
Section: Langevin Equationmentioning
confidence: 95%
“…Whereas in some complex viscoelastic mediums [29][30][31][32][33][34], such as actin filament networks [29], protein solutions [30][31][32], interiors of biological cells [33,34], anomalous diffusions have been widely observed, and it is characterized by the mean-square displacement satisfying ⟨x 2 (t)⟩ ∼ t α , where the diffusion exponents 0 < α < 1.0 and α > 1.0 respectively indicate subdiffusion [29][30][31][32][33][34][35][36][37][38] and super-diffusion [39], and α = 1.0 recovers the normal diffusion. Especially, the subdiffusion is experimentally firmly established in various mediums with different α in the range of 0.25 ∼ 1.0 [30][31][32][33][34]40,41]. It is found that the traditional coupled Brownian motors expressed by the integer order stochastic differential equations could not describe the complex transport behaviors of coupled particles under the background of anomalous diffusion.…”
Section: Introductionmentioning
confidence: 99%